New Records of Mosquitoes (Diptera: Culicidae) from Bolívar State in South Eastern Venezuela, with 27 New Species for the State and 5 of Them New in the Country - Berti, Jesús; Guzmán, Hernán; Estrada, Yarys; Ramírez, Rodrigo (Frontiers in Public Health, 2015)
This is the first part of a series of studies related to mosquito ecological and biogeographic aspects. A total of 69 mosquito species (Diptera: Culicidae) was collected in 16 localities sampled in the Gran Sabana Municipality, Canaima National Park, and Venezuela. Twenty-seven mosquito species are recorded for the first time from Bolívar State, Venezuela. Five of them species are reported for the first time in Venezuela: Anopheles malefactor Dyar and Knab (1907); Chagasia bonneae Root (1927); Chagasia ablusa Harbach (2009); Culex anduzei Lane (1944), and Uranotaenia leucoptera Theobald (1907). Their medical importance is commented, and ecological and epidemiological aspects are discussed. A checklist of the mosquito species reported in the Gran Sabana County is given.